2015
DOI: 10.5507/bp.2014.038
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of systemic and local inflammation parameters in talc pleurodesis assessment

Abstract: Background. One option for the palliative treatment of recurrent malignant pleural effusion is powdered talc using thoracoscopy. This paper presents the results of selected systemic and local manifestations of the talc-induced inflammatory reaction using a videothoracoscope. Method. A total of 114 patients with repeated malignant pleural effusion were treated at the Cardiac Surgery Clinic in Hradec Kralove from January 2010 to December 2012. Those with a life expectancy more than ≥ 3 months were eligible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The use of ECC may negatively infl uence many parameters of the immune system including leukocyte chemotaxis and cellmediated immunity, particularly T-lymphocytes (16). The use of…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ECC may negatively infl uence many parameters of the immune system including leukocyte chemotaxis and cellmediated immunity, particularly T-lymphocytes (16). The use of…”
Section: Discussionmentioning
confidence: 99%
“…The psychological aspect of the earlier enabled tumor resection. The negative impact of the ECC on the immune system, which can enhance tumor proliferation, is eliminated in case of simultaneous procedures (16,17). A certain benefi t of one-stage procedure performed via a median sternotomy is the ability to perform bilateral mediastinal lymphadenectomy, which has an important prognostic value.…”
Section: Table 5 Postoperative Outcome Of Complications and Mortalitymentioning
confidence: 99%
“…Psathakis et al [22] reported that pleural fluid neutrophils rose more profoundly after talc poudrage in the successful pleurodesis group in comparison to the failure group. The study by Habal et al [36] found that more pronounced increases in serum white cell count, and pleural fluid and serum CRP were seen in the success group in comparison to the failure group.…”
Section: Markers Of Inflammationmentioning
confidence: 93%
“…Three studies [22,24,36] examined the behaviour of blood and pleural fluid inflammatory markers in relation to pleurodesis outcome. Bilgin et al [24] found that erythrocyte sedimentation rate and blood C-reactive protein (CRP) values were increased in the postoperative period in patients with successful VATS pleurodesis but not in the failure group.…”
Section: Markers Of Inflammationmentioning
confidence: 99%
“…Small-particle talc was associated with higher inflammatory cytokine responses in one small non-randomised comparative study [37]. Interestingly, higher inflammatory responses were seen in patients following talc poudrage with successful pleurodesis compared with non-successful pleurodesis in a case series [38]. Similarly, higher fibrinolytic activity in pleural fluid has been associated with pleurodesis failure [39].…”
Section: Other Issues Regarding Talc Pleurodesismentioning
confidence: 99%